PELATIHAN TEKNIS APLIKASI SCREEN TIME & LOCATION TRACKER GUNA MEMANTAU DAN MELACAK PENGGUNAAN GADGET PADA ANAK - Fiby Nur Afiana; Jeffri Prayitno Bangkit Saputra; Farah Setyaningsih; El Syafangatun Aulia Difa (Yayasan Nusantara Hasana Berdikari, 2024)
Staring at a gadget screen too often can have a negative impact on a child's development and health. The consequence or impact of excessive use of gadgets in children is that it worsens the child's motor function abilities and increases the risk of early obesity. Daily screen time or known as daily screen time is a screen time management setting that allows parents to manage application usage. The problem that often occurs in some of the Association of Guardians of SDN 3 Purwanegara students is that on average they are working mothers, either office workers or traders who cannot supervise their children full twenty-four (24) hours. Sometimes after school they don't know where their children are, how long they use their gadgets, and they can't control what applications they access. The aim of this supervision is to protect children from the negative effects of using technology. Especially for working mothers who cannot supervise 24-hour gadget use and monitor their children's location. So that children can avoid bad things that can affect the future. Currently there are many Screen Time & Location Tracker applications that are applications to help parents manage their children's use of technology which can be controlled remotely. One of them is Find My Kids and Google Family Link. This allows parents to set a daily screen time limit to get notifications when that time has been reached and also helps parents know where their child is.